2013
DOI: 10.1007/s13197-013-1171-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmospheric packaging on chemical and microbial changes in dietetic rabri during storage

Abstract: Rabri is a dairy based sweet popular in the Indian subcontinent. The high sugar and fat content impose restrictions on its consumption due to health reasons. Dietetic rabri was prepared by the replacement of sugar with aspartame. Inulin was added to partially replace the milk fat and to improve the consistency of rabri. The rabri samples were packed in the polyethylene bags filled with different gaseous compositions (Air, 50 % CO2:50 % N2 and 100 % N2) and stored at 10°C. The shelf life was evaluated on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
6
12
0
Order By: Relevance
“…The delayed lipolysis in Kalakand samples stored under MAP could be attributed to the absence of oxygen in the package. Similar findings were reported by Londhe et al (2012), Jha et al (2013) and Ghayal et al (2013).…”
Section: Changes In Sensory Propertiessupporting
confidence: 91%
See 3 more Smart Citations
“…The delayed lipolysis in Kalakand samples stored under MAP could be attributed to the absence of oxygen in the package. Similar findings were reported by Londhe et al (2012), Jha et al (2013) and Ghayal et al (2013).…”
Section: Changes In Sensory Propertiessupporting
confidence: 91%
“…As Kalakand is a heat desiccated dairy product, oxidation may set in during the processing, thus increasing the TBA value. Similar observations were made by Ghayal et al (2013).…”
Section: Changes In Sensory Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…Quality and properties of packaging material affects shelf life of a food product. Several studies have been reported on increased shelf-life of traditional dairy products using spices and herbs (Londhe et al 2012 andGhayal et al 2015). Sweets like kalakand, milk-cake and other sweets have been packaged in paper cartons or duplex board boxes as reported by Goyal and Rajoriha (1991) to enhance shelf life.…”
Section: Introductionmentioning
confidence: 99%